Access to stereodefined (Z)-allylsilanes and (Z)-allylic alcohols via cobalt-catalyzed regioselective hydrosilylation of allenes - Chao Wang (Nature Portfolio, 2017)
Controlling selectivity in the hydrosilylation of allenes poses serious challenges in terms of product stereochemistry. Here the authors show that the title reaction proceeds with excellent (Z)-selectivity by use of a cobalt catalyst in the presence of phosphine-based ligands.